Pengaruh Digitalisasi Bank dan Kualitas Layanan terhadap Kepuasan Nasabah - Fadhlan Shidiq Al Adly; Nurhayati; Irena Paramita Pramono (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. The background of this research departs from the increasing use of digital banking services and the challenges in maintaining optimal service quality in the midst of the digital transformation process. The theoretical basis used is the Theory of Buyer Behavior, which states that consumer decisions are influenced by digital stimuli and perceptions of the quality of service. This research aims to examine the influence of banking digitalization and service quality on customer satisfaction, especially in the millennial generation and generation Z in the city of Bandung. The method used is quantitative with a verifiable approach. The data was collected by distributing questionnaires to 107 respondents who are users of mobile banking services in Bandung. Data processing and analysis were carried out using the StructuraI Equation Modeling–PartiaI Least Square (SEM-PLS) approach. The results of the study show that bank digitalization and service quality have a positive and significant effect on customer satisfaction. An R² value of 0.586 indicates a moderate influence of the two independent variables on customer satisfaction. Based on these findings, it is recommended that banking institutions continue to develop user-friendly digital innovations and increase training for service staff so that interactions with customers remain quality in the digital era. Abstrak. Meningkatnya adopsi layanan perbankan digital dan tantangan menjaga kualitas layanan selama proses transformasi digital. Kerangka teori yang digunakan adalah Teori Perilaku Pembeli, yang menunjukkan bahwa keputusan konsumen dipengaruhi oleh stimulus digital dan persepsi mereka tentang kualitas layanan. Penelitian ini bertujuan untuk mengkaji pengaruh digitalisasi bank dan kualitas layanan terhadap kepuasan nasabah, khususnya di kalangan milenial dan Generasi Z di Kota Bandung. Metode kuantitatif dengan pendekatan verifaktif diterapkan. Data dikumpulkan melalui kuesioner yang disebarkan kepada 107 responden yang menggunakan layanan mobile banking di Bandung. Data diproses dan dianalisis menggunakan Structural Equation Modeling–PartiaI Least Square (SEM-PLS). Temuan tersebut menunjukkan bahwa digitalisasi bank dan kualitas layanan memiliki dampak positif dan signifikan terhadap kepuasan nasabah. Analisis model menunjukkan nilai R² 0,586, yang dikategorikan sebagai tingkat infIuence sedang. Berdasarkan hasil tersebut, disarankan agar lembaga perbankan terus mengembangkan inovasi digital yang ramah pengguna dan meningkatkan pelatihan staf layanan untuk memastikan interaksi nasabah yang berkualitas tinggi di era digital.